2023
DOI: 10.5194/egusphere-2022-1425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing land elevation in the Ayeyarwady Delta (Myanmar) and its relevance for studying sea level rise and delta flooding

Abstract: Abstract. With their low lying, flat topography, river deltas and coastal plains are extremely prone to relative sea level rise and other water related hazards. This calls for accurate elevation data for flood risk assessments, especially in the densely populated Southeast Asian deltas. However, in data-poor countries such as Myanmar, where high accuracy elevation data is not accessible, often only global satellite based digital elevation models (DEMs), suffering from low vertical accuracy and remote sensing a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 64 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Such a difference has obviously major consequences when assessing what is at risk for different levels of rSLR. A recent study on the Ayeyarwady delta revealed similar large discrepancies between different global DEM and local control data 90 . On a global scale, attempts are being made to improve existing global DEMs for the coastal zones, for example using machine-learning 91,92 or interpolating space-borne LiDAR data (I.e.…”
Section: Global Trends and Models For Key Drivers Of Relative Sea Lev...mentioning
confidence: 81%
See 1 more Smart Citation
“…Such a difference has obviously major consequences when assessing what is at risk for different levels of rSLR. A recent study on the Ayeyarwady delta revealed similar large discrepancies between different global DEM and local control data 90 . On a global scale, attempts are being made to improve existing global DEMs for the coastal zones, for example using machine-learning 91,92 or interpolating space-borne LiDAR data (I.e.…”
Section: Global Trends and Models For Key Drivers Of Relative Sea Lev...mentioning
confidence: 81%
“…ICEsat 2) for the coastal zone 93 . Such products allow improved modeling of coastal and delta products than "raw" DEMs but they should be validated using local groundtruth data, as large discrepancies may still occur 89,90 , and need to be updated periodically to reflect latest developments in land subsidence 28 . Discovering opportunities to curb rSLR will not only rely on better data, but also on new types of numerical modeling approaches.…”
Section: Global Trends and Models For Key Drivers Of Relative Sea Lev...mentioning
confidence: 99%
“…The related data was obtained via the freely accessible global flood database from Tellman et al (2021). To consider RSLR in the hazard assessment, we used a RSLR scenario of 1 m to map areas falling below sea level based on a locally improved FABDEM from Seeger et al (2023b). The exposure to multiple flooding was assessed through two scenarios: The short-term scenario included monsoon flood frequency and storm surge flooding while the mid-to long-term scenario also integrated the impact of RSLR.…”
Section: Methodsmentioning
confidence: 99%
“…FABDEM was created with a three-step algorithm to remove signals of forests and buildings from the 30-m Copernicus DEM (COPDEM30) 20 . FABDEM outperformed other global DEMs in deltaic flood models due to its better estimation of delta surface heights and a lack of striping or other artifacts 36,37 . Crucially, FABDEM was originally validated using ICESat-2 ATL08 data, showing good alignment with a mean error of -0.03 m and an error percentage < 2m of 80.42%.…”
Section: Topographic Datasetsmentioning
confidence: 99%